The Impact of Import Tariffs on Economic Growth in Indonesia: Evidence from Provincial Panel Data (2010-2024) - Dhika Sanjaya; Guntur Eko Saputro; Suwito Suwito (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study examines the impact of import tariff policy on Indonesia’s economic growth over the 2010–2024 period, aiming to provide an empirical foundation for designing adaptive tariff strategies that balance efficiency and industrial protection. A quantitative explanatory approach is employed using panel data from 34 provinces. Secondary data were obtained from official open sources, including Statistics Indonesia (BPS), the Directorate General of Customs and Excise (DJBC), the World Integrated Trade Solution (WITS), and the World Bank. The analysis utilizes Fixed and Random Effect Models, with the Hausman test determining the optimal specification. The results indicate that higher import tariffs suppress Indonesia’s economic growth by increasing input costs and reducing industrial productivity. Investment and exports exhibit positive effects, while exchange rate depreciation negatively affects growth, particularly in import-dependent sectors. Notably, moderate tariffs can play a strategic role in protecting emerging industries that contribute to structural transformation and long-term competitiveness. The findings underscore the need for adaptive tariff policies lowering tariffs on raw materials and capital goods while maintaining moderate protection for strategic sectors such as manufacturing and agro-processing. Such policies can enhance productivity, attract investment, and foster sustainable growth across Indonesia’s regions. This study advances the literature by combining provincial-level panel data with a robust econometric framework to quantify the effects of tariff adjustments on economic growth. It bridges theory and policy by demonstrating how selective liberalization, grounded in endogenous growth dynamics, can optimize Indonesia’s trade strategy for sustainable and inclusive development.